HOTEL EMPLOYEE PERFORMANCE DURING COVID-19 - Hafidulloh Hafidulloh; Mochamad Mochklas; Rina Maretasari; Netri Mawarsari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
During the Covid-19 pandemic, the hotel sector was severely affected by around 95% of hoteliers who laid off their employees or gave unpaid leave. Employees have an active role in setting plans, systems, processes, and goals to be achieved. In order for the hotel sector to survive, high employee performance is needed, to determine the level of employee performance, it is necessary to analyze work motivation and emotional intelligence. This study uses a quantitative approach and uses multiple linear regression analysis methods, where the population in this study is one of the 3 star hotel employees. The results in this study indicate that work motivation has a positive and insignificant effect on employee performance, emotional intelligence has a positive and significant effect on employee performance, motivation and emotional intelligence have a positive and significant effect on employee performance